2014
DOI: 10.1371/journal.ppat.1004466
|View full text |Cite
|
Sign up to set email alerts
|

HPV16-E7 Expression in Squamous Epithelium Creates a Local Immune Suppressive Environment via CCL2- and CCL5- Mediated Recruitment of Mast Cells

Abstract: Human Papillomavirus (HPV) 16 E7 protein promotes the transformation of HPV infected epithelium to malignancy. Here, we use a murine model in which the E7 protein of HPV16 is expressed as a transgene in epithelium to show that mast cells are recruited to the basal layer of E7-expressing epithelium, and that this recruitment is dependent on the epithelial hyperproliferation induced by E7 by inactivating Rb dependent cell cycle regulation. E7 induced epithelial hyperplasia is associated with increased epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 62 publications
(87 reference statements)
3
77
0
Order By: Relevance
“…A proximal gamma interferon activation site (GAS) element in the IL-18BP promoter is responsible for IL-18BP transactivation by E7, indicating that IFN-γ signaling might be critical for increased expression of immunosuppressive genes, including IL-18BP and IDO1. A recent study has shown that transgenic mice expressing HPV16 E7 have increased epidermal secretion of the chemokines CCL2 and CCL5, which recruit mast cells expressing CCR2 and CCR5, the receptors of CCL2 and CCL5, respectively (Bergot et al, 2014). Mast cells in HPV16 E7-expressing transgenic skin generate an immunosuppressive environment resulting in significantly reduced graft rejection (Bergot et al, 2014).…”
Section: Immune Evasion By Altering Host Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proximal gamma interferon activation site (GAS) element in the IL-18BP promoter is responsible for IL-18BP transactivation by E7, indicating that IFN-γ signaling might be critical for increased expression of immunosuppressive genes, including IL-18BP and IDO1. A recent study has shown that transgenic mice expressing HPV16 E7 have increased epidermal secretion of the chemokines CCL2 and CCL5, which recruit mast cells expressing CCR2 and CCR5, the receptors of CCL2 and CCL5, respectively (Bergot et al, 2014). Mast cells in HPV16 E7-expressing transgenic skin generate an immunosuppressive environment resulting in significantly reduced graft rejection (Bergot et al, 2014).…”
Section: Immune Evasion By Altering Host Gene Expressionmentioning
confidence: 99%
“…A recent study has shown that transgenic mice expressing HPV16 E7 have increased epidermal secretion of the chemokines CCL2 and CCL5, which recruit mast cells expressing CCR2 and CCR5, the receptors of CCL2 and CCL5, respectively (Bergot et al, 2014). Mast cells in HPV16 E7-expressing transgenic skin generate an immunosuppressive environment resulting in significantly reduced graft rejection (Bergot et al, 2014). Contrastingly, a previous study has shown that retroviral transduction of HPV16 E6 and E7 almost completely shut down CCL2 expression in primary cervical epithelial cells (Kleine-Lowinski et al, 2003).…”
Section: Immune Evasion By Altering Host Gene Expressionmentioning
confidence: 99%
“…Ear to flank skin grafts (groups of five mice) and assessment of graft outcomes to 50 days post grafting were performed as previously described (16). …”
Section: Methodsmentioning
confidence: 99%
“…Despite being immunosuppressive, HPV infection is also mildly inflammatory, and inflammation increases during progression to high-grade lesions 208 . Biopsies of women with high risk HPVs or mice expressing HPV oncogenes in the skin show greater inflammation within the epithelium compared to HPV negative controls and moderate stromal inflammation as defined by immune cell infiltration 209212 . The levels of a wide range of cytokines and other secreted factors are increased in the cervical secretions of women with HPV infection in the cervix, including IL8, VEGF, IL12, interferon (IFN)-α2, M-CSF, and G-CSF 213 .…”
Section: Immune Interactionsmentioning
confidence: 99%
“…Whether HPV infection actually causes TAM development is not known, but macrophages with TAM markers infiltrate the epithelium and stroma of HPV-containing lesions, secrete pro-angiogenic IL8 and VEGF, and suppress T cell responses 379384 . HPV can also interfere with the functions of DCs 293,294,321 , mast cells 212 , and NK cells 345,385,386 .…”
Section: Immune Interactionsmentioning
confidence: 99%